PENINGKATAN KEMAMPUAN APRESIASI PUISI DENGAN TEKNIK DEKLAMASI PADA SISWA KELAS V SD NEGERI 41 BENGKULU SELATAN - Yahmo, Yahmo (UNIB Press, 2015)
The aim of this research is to improve the ability and activity ofgrade 5 Students Elementary School 41 South Bengkulu especially in poetry.This research is an action researchwhich was in September untilNopember 2011. The Subject of this research are 19students in Elementary SchoolSouth Bengkulu. The data source was used areinformant and document. The data analysis technique used the data reduction, explanation , and conclusion. Base of studying score list results, can be concluded that the improvementof studying quality in poetry consciousness poetries which used teaching aide declamation.It was indicated by (1). The studying processwos not in one direction, (2). The students were more enthusiastics to follow the lesson,(3) And the students were more active and attentive to response the teacher questioner. And then, it was indicated by the improvement average. Score of students if was compored with observation. Which in first cycle were 51,58 or 52 and second cycle 53,68 or 54 one action and 71,58 or 72 two action.Keywords: ability improvement poetry, technics declamation